Intra-household discrete choice experiment for trait preferences: a new method - Mukerjee, Rishabh; Fatou Faye, Ndeye; Badji, Malamine J.; Gomez, Miguel; Rubin, Deborah; Tufan, Hale Ann; Occelli, Martina (Frontiers Media, 2023)
Crop trait and varietal preferences are socially shaped, varying by gender, experience, and on-farm roles. This drives preference heterogeneity, between households but also within households. Adhering to the common practice of only interviewing the household head as a representative of households, leads to breeding programs collecting trait preferences that do not represent the experiences of other members within that household. This dearth of data on trait preferences of multiple household members could be hindered by the lack of robust and agile methods to collect this data. Here we present a method that explores intra-household differences between husbands and wives in trait preferences through choice experimentation, coupled with questions that capture decision-making, experience and time spent on farm to explore how these drive preferences. Dissecting crop management into three dimensions, we explore what drives intra-household heterogeneity in varietal preferences between husbands and wives, as well as, decision-making, crop experience and time spent working on the crop. We present preliminary results from testing this combined protocol with 270 cowpea growing households (540 respondents) in Senegal. The findings from this work hold promise to inform crop breeding programs on the value of intra-household analysis for trait priority setting, while offering a new method which is applicable by National Agricultural Research Organizations globally.